Experimental and analytical evaluation of the in-plane behaviour of as-built and strengthened traditional wooden floors. (15th May 2020) - Mirra, Michele; Ravenshorst, Geert; van de Kuilen, Jan-Willem
Highlights: As-built flexible timber diaphragms may be not suitably regarded as shear walls. A plywood panels overlay increases the dissipative properties of timber diaphragms. A single value of stiffness cannot properly describe the nonlinear floors' response. Orthotropic behaviour of timber diaphragms is strongly mitigated after strengthening. Abstract: Traditional timber floors cannot normally withstand horizontal seismic loads without large deformations. This may lead to a corresponding out-of-plane collapse of masonry walls in existing buildings. This situation is even more critical in the Netherlands, around the city of Groningen, where human-induced earthquakes started to take place. Since no seismic events have been experienced until recently, none of the existing buildings was designed with seismic events in mind, with no exception for the timber floors: therefore, it was necessary to characterize their in-plane response. To obtain representative results, firstly floor and roof samples were extracted from existing buildings. The relevant material properties were determined, together with the plank-joist connections behaviour. Replicas were then built with new material and tested to confirm the similarity in response compared to extracted samples. Based on these results, full-scale replicated diaphragms were constructed, and tested quasi-static reversed-cyclic in their plane, either parallel or perpendicular to the joists. Besides characterizing as-built diaphragms, a simple strengthening technique with plywood panels was applied as well, improving their in-plane response in terms of strength, stiffness and energy dissipation, as test results confirm. This study is concluded with an analytical characterization of the diaphragms' in-plane response, for as-built and strengthened configurations.